Integration of Ngasa Tradition as Local Wisdom in Strengthening Character in Elementary Schools - Susanto, Ari; Handoyo, Eko; Wasino, Wasino (Jurnal Ilmiah Wahana Pendidikan, 2025)
This research aims to integrate Ngasa tradition as local wisdom in strengthening student character in elementary schools. Ngasa tradition, which is rich with cultural values such as mutual cooperation, environmental awareness, and spirituality, has high relevance to shape the character of the younger generation in accordance with the nation's culture. The approach used was qualitative research with explorative descriptive method. The research subjects included teachers, students, school principals, and traditional leaders involved in the implementation of the Ngasa tradition. Data were collected through observation, in-depth interviews, and documentation, then analyzed thematically using the Juran Framework Analysis. The results show that Ngasa tradition can be implemented in learning through various culture-based activities, such as discussion of traditional values, group projects, and direct engagement with indigenous communities. This integration not only improves students' understanding of moral and social values, but also strengthens students' character in terms of responsibility, cooperation, and respect for local culture. This research makes an important contribution to the development of local wisdom-based learning models that are relevant to the needs of modern education, while supporting the preservation of traditional culture in Indonesia..